2010
DOI: 10.1507/endocrj.k10e-281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PPAR.GAMMA. on hypertension, atherosclerosis, and chronic kidney disease

Abstract: Abstract. Peroxisome proliferator-activated receptor (PPAR) γ is a nuclear hormone receptor that is trans-activated by its ligands including insulin-sensitizing thiazolidinediones. PPARγ has recently been reported to demonstrate pleiotropic beneficial effects in the vasculatures, independent of its blood glucose-lowering effects. Firstly, PPARγ ligands have been shown to lower blood pressure in both animals and human. The effect may possibly be mediated via the PPARγ-mediated inhibition of the angiotensin (Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…These MAPKsw activate a series of cascades involved in inflammation and IR. Interestingly, they appear to block the function of PPARγ via its phosphorylation [34,35]. Corroborating with this, we saw higher activation of ERK1/2 and JNK in the HF-L group associated with increased phosphorylation of PPARγ, which can justify the alterations in insulin signaling, glucose tolerance and inflammation seen in the current study.…”
Section: Discussionsupporting
confidence: 82%
“…These MAPKsw activate a series of cascades involved in inflammation and IR. Interestingly, they appear to block the function of PPARγ via its phosphorylation [34,35]. Corroborating with this, we saw higher activation of ERK1/2 and JNK in the HF-L group associated with increased phosphorylation of PPARγ, which can justify the alterations in insulin signaling, glucose tolerance and inflammation seen in the current study.…”
Section: Discussionsupporting
confidence: 82%
“…Activation of hepatic AMPK leads to increased fatty acid oxidation and simultaneously inhibition of hepatic lipogenesis, cholesterol synthesis and glucose production (Viollet et al, 2009;Wang et al, 2011b). These AMPK-dependent alterations in lipid metabolism are involved in the action mechanism of many therapeutic agents, such as thiazolidinediones and statins (Schimmack et al, 2006;Sugawara et al, 2010;Ewart and Kennedy, 2011). Besides reducing lipid accumulation and fatty acid metabolism in liver and skeletal muscle (Thomson and Winder, 2009), recent studies have provided proof of concept for the idea that AMPK is a therapeutic target of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the SOs on proliferation and apoptosis of these colon cancer cells were attributed to both PPAR␥-dependent and -independent mechanisms, and several other investigators have suggested that SO-PPAR␥ interactions may decrease levels of cyclin D1 or induce caveolin-1 (Lapillonne et al, 2003;Konopleva et al, 2006). PPAR␥ has been suggested as a possible therapeutic target for diseases as diverse as diabetes, atherosclerosis, hypertension, chronic kidney disease, and cancer (Glass, 2006;Glass and Ogawa, 2006;Schmidt et al, 2010;Sugawara et al, 2010). It is noteworthy that 15-deoxy-⌬ 12,14 -PGJ2 covalently binds to a cysteine residue in the ligand binding pocket of PPAR␥ through Michael addition (Shiraki et al, 2005); the ability of an SOs to interact with this Cys residue has not been confirmed.…”
Section: B Peroxisome Proliferator-activated Receptor ␥ (Ppar␥)mentioning
confidence: 99%